RESONANCE BEHAVIOUR ANALYSIS OF CARRYING SYSTEM IN HEAVY MACHINE WITH TRAVELING-COLUMN - Yu. V. Vasilevich; S. S. Dovnar (Наука и техника, 2015)
A finite elements method (FEM)-analysis has been carried out with the purpose to study dynamics of carrying system in a machine tool of unique height. This is a one-off machine with high traveling column and a support with horizontal slide can move vertically along the column. Spindle milling and boring units are mounted telescopically at slide butt end. The FEM-analysis of the machine tool has been made due to its renovation. Machine resonances, responses to cutting force, static and dynamic rigidity in spindles have been estimated in the paper. The machine carrying system is subtle, heavy and structurally complicated. Its structural chain includes a carriage, a column, a support, a slide, spindle units interconnected with the help of hydro-static guides. While varying main parameters their influence on rigidity has been investigated in the paper. Height of  support lifting, column material and rigidity of longitudinal drive have been changed during the investigations.Static, modal and harmonic MEF-analyses have been executed in the paper. Frequency-response characteristic of the machine has been constructed in the process of the investigations. Two support bending resonances have been detected in the column at low frequency. Such Due to this there are limits for usage of the machine in sub-resonance and static frequency range. The most powerful resonance has been observed at frequency of 27.8 Hz. The resonance has manifested itself as torsional oscillations of the column together with the support and the slide.Slide bending resonances have been revealed at higher frequencies 65–105 Hz. Three intervals which are fit for machine operation have been determined between resonance ranges. There is a prospective usage of the machine in inter-resonance (32–65 Hz) and super-resonance (more than 105 Hz) intervals. It has been shown that rigidity in spindle is a sequence higher in dynamic intervals than in a static interval. Machine subtility can be compensated by its transition to high-speed machining.